2000
DOI: 10.1007/pl00008887
|View full text |Cite
|
Sign up to set email alerts
|

Competition intensity and its importance: results of field experiments with Anthoxanthum odoratum

Abstract: The effect of community productivity on competition was studied in 82 permanent plots using two removal experiments with the rhizomatous perennial grass Anthoxanthum odoratum. The removal of neighbouring plants had a positive effect on the number of shoots and total above-ground biomass of Anthoxanthum but no significant effect on mean shoot biomass. The relative competition intensity coefficient (RCI) calculated from these data showed that competition intensity increased with increasing community productivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 46 publications
10
64
1
1
Order By: Relevance
“…Our results support the view of Mulder et al (2004) that minor species may have little ability to increase productivity in the absence of common species and of Smith and Knapp (2003) that dominant species can maintain a high biomass production in the absence of rare and uncommon species. These opposing impacts of neighbor removal on dominant versus minor species may explain why responses to neighbor removal are not consistent, ranging from positive (Sammul et al 2000;Gerdol et al 2002), to neutral (BretHarte et al 2004Totland et al 2004), to negative (Shevtsova et al 1997;Aksenova et al 1998). In general, our results support our Wrst two hypotheses: removing species has much greater impacts than removing an equivalent amount of biomass, and dominant species are more able to respond to this treatment than minor species.…”
Section: Biomass Changes Following Removal Treatments: Dominant Versusupporting
confidence: 85%
“…Our results support the view of Mulder et al (2004) that minor species may have little ability to increase productivity in the absence of common species and of Smith and Knapp (2003) that dominant species can maintain a high biomass production in the absence of rare and uncommon species. These opposing impacts of neighbor removal on dominant versus minor species may explain why responses to neighbor removal are not consistent, ranging from positive (Sammul et al 2000;Gerdol et al 2002), to neutral (BretHarte et al 2004Totland et al 2004), to negative (Shevtsova et al 1997;Aksenova et al 1998). In general, our results support our Wrst two hypotheses: removing species has much greater impacts than removing an equivalent amount of biomass, and dominant species are more able to respond to this treatment than minor species.…”
Section: Biomass Changes Following Removal Treatments: Dominant Versusupporting
confidence: 85%
“…All plants were allowed to grow for 75 days before harvest. Because the roots of C. lasiocarpa and D. angustifolia in the mixtures were closely intertwined, only the aboveground portions were harvested in the mixture as described previously (Fowler 1982;Sammul et al 2000;Garcia-Serrano et al 2007). After harvest, plants in the monoculture were divided into aboveground and belowground portions while aboveground portions in the mixture were divided into C. lasiocarpa and D. angustifolia.…”
Section: Plant Materials and Experimental Designmentioning
confidence: 99%
“…In a comparison of three plant species C imp decreased with fertility but it was suggested that competitive importance was dependent on the ability of the species to tolerate low resource availability (Gaucherand et al 2006). Sammul et al (2000), using a different calculation of competitive importance, reported a correlation between both C int and C imp when competition was calculated using the number of shoots rather than biomass, and Welden et al (1988) detected no relationship between importance or intensity and a water stress gradient for desert shrubs. We observed a reduction in competitive importance due to clipping under the high resource conditions for F. campestris, which further supports arguments that competition in CSR theory is best measured with this index because the measure of competition declines when additional processes are in place.…”
Section: Competitive Intensity and Competitive Importancementioning
confidence: 99%